BIODIVERSITY REVIEW FROM EVOLUTION AND ITS INFLUENCES ON CLIMATE - Jamilah Nasution; Ferdinand Susilo; Nurmaini Ginting; Radiansyah Hadi Chandra (Universitas Negeri Medan, 2022)
Biodiversity refers to the variety of organisms, including genes, species, and ecosystems in a given area. Biodiversity plays an important role in evolutionary processes and in maintaining the balance between the biosphere ecosystem and biological systems. Climate change is equally important to contribute to the sustainability of biodiversity. Factors causing ecosystem damage include human population, habitat conversion and transformation, overexploitation, invasive species, pollution, and climate change. By stopping the rate of loss of biodiversity that is occurring in the world, it will automatically invest in the survival and welfare of every human being.